Developing School Leaders: Findings From a Randomized Control Trial Study of the Executive Development Program and Paired Coaching. (June 2022) - Master, Benjamin K.; Schwartz, Heather; Unlu, Fatih; Schweig, Jonathan; Mariano, Louis T.; Coe, Jessie; Wang, Elaine Lin; Phillips, Brian; Berglund, Tiffany
Principals are the second-largest school-based contributor to K–12 students' academic progress. However, there is little research evaluating whether efforts to develop principals' skills improve school effectiveness. We conducted randomized controlled trial studies of the impacts of a professional development program called the Executive Development Program (EDP) and of the incremental effects of coaching to help principals implement the EDP curriculum. We find that the EDP alone influenced principals' practices, but not student achievement, within 3 years. Coaching had a small positive effect on students' English Language Arts achievement, but no effect on math achievement or on principals' practices. Coaching had the largest effects in disadvantaged schools. We hypothesize that coaching enhanced the quality of implementation of recommended practices.